2008
DOI: 10.1089/aid.2008.0153
|View full text |Cite
|
Sign up to set email alerts
|

High Divergence within the Major HIV Type 1 Subtype B Epidemic in Panama

Abstract: The first molecular epidemiology study of human immunodeficiency virus type 1 (HIV-1) in Panama has been performed with plasma samples from 66 AIDS patients infected by different transmission routes and obtained from distinct locations. All samples were amplified by RT-PCR and sequenced in gag (p17) and env (C2-C4) genes. Phylogenetic analyses revealed that 64 (97%) of the samples belong to subtype B. We also identified the presence of two CRF, one CRF12_BF and one CRF02_AG. The most notable feature of the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…In our study, we found that the Panamanian HIV epidemic is driven predominantly by HIV-1 subtype B, confirming the previous study [16]; but we also described for the first time the circulation of several non-B variants at very low prevalence (≤ 0.5%) that were classified as subtype F1, subtype C, CRF 20_BG, CRF28/29_BF and URFs_BC. Thus, the HIV-1 molecular epidemiology scenario in Panama is more complex than previously described [16], [17]; this is most likely due to the much larger number of sequences analyzed in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we found that the Panamanian HIV epidemic is driven predominantly by HIV-1 subtype B, confirming the previous study [16]; but we also described for the first time the circulation of several non-B variants at very low prevalence (≤ 0.5%) that were classified as subtype F1, subtype C, CRF 20_BG, CRF28/29_BF and URFs_BC. Thus, the HIV-1 molecular epidemiology scenario in Panama is more complex than previously described [16], [17]; this is most likely due to the much larger number of sequences analyzed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the genetic diversity of HIV-1 in Panama is expected to resemble the diverse genetic profile observed in other parts of the Americas and the Caribbean. The only other HIV-1 molecular epidemiologic survey performed in Panama to date, analyzed the gag , pol , and env genes of 133 samples collected between 2004 and 2005, reporting a high prevalence of subtype B (97%) and only two cases of non-B-subtypes (one CRF12_BF and one CRF02_AG) [16], [17]. The aim of our study was to expand our comprehension of the HIV-1 subtype distribution in Panama by the phylogenetic analysis of the pol region of a large number of individuals ( n  =  655) from different regions of the country that were diagnosed over a long time period (1987–2013).…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that subtype B is predominant in the region, which is congruent with reports from neighboring countries such as Mexico, Colombia, and Venezuela (45)(46)(47), as well as smaller reports from Central America (14)(15)(16)(17). Interestingly, however, while HIV-1 group M subtype B strains worldwide usually intermix in a star-like phylogeny, indicative of the panmictic structure of the epidemic, strains from Central America appeared to be highly compartmentalized.…”
Section: Discussionsupporting
confidence: 83%
“…HIV-1 group M subtype B dominates the epidemics in North America and Western and Central Europe, whereas subtype B and BF recombinants predominate in South America (13). The information on the molecular epidemiology of HIV-1 in Central America is still limited, but available data suggest that HIV-1 group M subtype B predominates (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Estimates of genetic distance were used to evaluate genetic divergence between hMPV subtypes [26]. The overall mean distances of the hMPV subtypes were estimated using MEGA (version 4.0) [27].…”
Section: Methodsmentioning
confidence: 99%